The Implementation of Hisbah Among Marriage Consultation Officers in Kelantan:An Analytical Syudy of Hadith Perspective and Al-Ghazali Theory - Nurul Hanis Sufia Bt Othman
Disagreement in marriage life is ordinary, but if left prolonged without efforts to settle the situation, a small problem can spread to major upheavals and eventually lead to divorce. Hence, this is the function of the Marriage Consultation Unit under the Islamic Religious Department in every state of Malaysia. During any marriage dispute, the appointed consultation officer (CO) normally acts as a counsellor to listen to the issues of both parties and provide advice to reconcile the marriage relationship between husband and wife. However, the CO is not among the accredited counsellors even though counselling practices are implemented during the session. Thus, many people blame the CO due to various unsuccessful marriage reconciliation that lead to higher statistical divorce rate in Malaysia. This phenomenon triggered the researcher to study the implementation of Islamic counselling among the CO known as hisbah, which focuses on the al-Ghazali's theories of five elements of purification of the soul in hisbah. These are; musyaratah, muraqabah, muhasabah, mujahadah, and mu 'atabah. Also, the four main objectives to be achieved in this study are to explore the hadiths related to theories al-Ghazali's five elements in hisbah, to study the understanding of the CO of the elements in hisbah, to examine how far the CO implement the concept of hisbah in the marriage consultation session, and to analyse the obstacles faced by them in implementing this concept. This study is a qualitative research that employed the use of document analysis method, interviews and observation. Document analysis was used to extract hadiths related to elements in hisbah from the selected books. In which six CO from six districts of Kelantan participated to be interviewed in this research and observation made. The findings showed that there are 29 hadiths related to hisbah and 42 hadiths supporting al-Ghazali's theories elements in hisbah. Most of the CO also know and implement those elements. However, there are a few of them do not know certain elements and agreed to implement it in the next time. Besides that, there are four aspects of obstacles faced by them to practise it in marriage consultation which are obstacles from the CO itself, obstacles from clients, obstacles from netizens and obstacles related to time. Hence, it is hoped that this study would add to the existing literature of hisbah as well as its implementation in counselling. Through this study also, the techniques used in marriage consultation is expected to be more effective and hopefully lead to the reduction of divorce statistics in Kelantan and throughout the country.